Temperature sensing scheme based on fiber ring microwave photonic filter with erbium doped fiber amplification. Issue 4 (27th December 2019) - Yang, Shangwu; Xiang, Zhuowei; Fu, Hongyan; Wang, Yunfeng
Abstract: The temperature sensing scheme based on fiber ring microwave photonic filter (MPF) with erbium doped fiber amplification (EDFA) is proposed and experimentally demonstrated. The fiber ring is used as the time delay element, as well as a sensing element, and by introducing an EDFA to compensate the loss in the fiber ring, the number of the effective sampling taps and thus the suppression ratio are increased. When the EDFA power is set at 0.74 mW, the 3 dB bandwidth of the passband and suppression ratio of the MPF are estimated to be 82.5 kHz, and 15 dB, respectively. The superior sharp passband characteristics make the fiber ring MPF with an EDFA very advantageous for sensing. In our experiment, temperature sensing by using the fiber ring MPF with an EDFA has been carried out for demonstration. The temperature variations induce refractive index changes of the fiber, which will change the time delay of each tap of the fiber ring MPF, and as a result, the FSR of the MPF will be changed. By tracing the peak point shift of the MPF's passband, the temperature variations can be monitored. Our experimental results show that there is a good linear relationship between temperature change and frequency shift, and by measuring passbands with different frequencies, different sensitivity can be obtained. In our experiment, the sensitivity is estimated to be −5.89, −11.74, and − 17.7 kHz/°C, respectively, when the passbands at 0.8, 1.6, and 2.4 GHz are adopted for temperature monitoring.